Religieuse pluraliteit en waarheid: die hoofstroom Christelike respons - D. J. Louw (Acta Theologica)
Our shrinking world confronts us with a plurality of religions of which all claim to be "true". How should we evaluate these claims? The mainstream Christian response to this question oscillates between exclusivism and inclusivism. These responses are explained and evaluated with reference to Karl Barth (conservative exclusivism), Hendrik Kraemer and Emil Brunner (liberal exclusivism) and Karl Rahner (inclusivism). It is concluded that the responses of both the exlusivist and inclusivist boil down to the very subjective arbitrariness that they wish to avoid.